Women Leading Microenterprises in Chile. The Challenge of Formalization from a Gender Perspective - Ruiz-Martínez, Rocío (2022)
Micro-entrepreneurship  in  Latin  America  and  the  Caribbean  plays  a  dominant  role  to  an  economic  and  social  extent.  This  organizations'  segment  exhibits  high  rates  of  informality  and  precariousness  in  their  activities,  whose  magnitude  has  far-reaching  implications  in  societies  characterized  by  substantive  gender  inequality.  In  turn,  the  impact  of  the  COVID-19  pandemic  on  the  informal  economy  in  Latin  America  has  become  relevant  due  to  its  different  implications.  Also,  it  reveals  future  challenges,  so  it  is  pertinent  to  identify  aspects  underlying  this  impact  that  drive  and/or  limit  the  conditions  for  formalizing  the  entrepreneurship.  The  aim  of  this  study  is  to  identify  the variables that affect the formalization of microenterprises in Chile in the prepandemic scenario and to explore differences between microenterprises led by men and women. Applying a probit econometric model, aggregate results reveal drivers related to keeping accounting  records,  income  levels  above  the  minimum  wage  or  intellectual  capital,  which would increase the probability of formalizing in both groups; however, the gender gap  in  income  level  would  leave  women  behind.  On  the  other  hand,  the  probability  of  formalizing  decreases  while  the  number  of  hours  of  unpaid  work  increases,  one  variable  that  affects  women  to  a  greater  extent,  who  practically  triple  the  number  of  hours  dedicated  by  the  men  to  these  activities.  The  article  demands  the  use  of  the  gender perspective as the key factor for research. Finally, directions for public policies and further research are suggested.